Influence of Plasma Cell Niche Factors on the Recruitment and Maintenance of IRF4(hi) Plasma Cells and Plasmablasts in Vaccinated, Simian Immunodeficiency Virus-Infected Rhesus Macaques with Low and High Viremia - Shaw, Julia M. (J Virol, 2017)
In a recent study, we found that protection following simian immunodeficiency virus (SIV) exposure correlated with rectal plasma cell frequency in vaccinated female rhesus macaques. We sought to determine if the same macaques maintained high mucosal plasma cell frequencies postinfection and if this translated to reduced viremia. Although delayed SIV acquisition did not predict subsequent viral control, alterations existed in the distribution of plasma cells and plasmablasts between macaques that exhibited high or low viremia. Flow cytometric analysis of cells from rectal biopsy specimens, bone marrow, and mesenteric lymph nodes of vaccinated infected, unvaccinated infected, and uninfected macaques identified two main IRF4(hi) subsets of interest: CD138(+) plasma cells, and CD138(−) plasmablasts. In rectal tissue, plasma cell frequency positively correlated with plasma viremia and unvaccinated macaques had increased plasma cells and plasmablasts compared to vaccinated animals. Likewise, plasmablast frequency in the mesenteric lymph node correlated with viremia. However, in bone marrow, plasmablast frequency negatively correlated with viremia. Accordingly, low-viremic macaques had a higher frequency of both bone marrow IRF4(hi) subsets than did animals with high viremia. Significant reciprocal relationships between rectal and bone marrow plasmablasts suggested that efficient trafficking to the bone marrow as opposed to the rectal mucosa was linked to viral control. mRNA expression analysis of proteins involved in establishment of plasma cell niches in sorted bone marrow and rectal cell populations further supported this model and revealed differential mRNA expression patterns in these tissues. IMPORTANCE As key antibody producers, plasma cells and plasmablasts are critical components of vaccine-induced immunity to human immunodeficiency virus type 1 (HIV-1) in humans and SIV in the macaque model; however, few have attempted to examine the role of these cells in viral suppression postinfection. Our results suggest that plasmablast trafficking to and retention in the bone marrow play a previously unappreciated role in viral control and contrast the potential contribution of mucosal plasma cells to mediate protection at sites of infection with that of bone marrow plasmablasts and plasma cells to control viremia during chronic infection. Manipulation of niche factors influencing the distribution and maintenance of these critical antibody-secreting cells may serve as potential therapeutic targets to enhance antiviral responses postvaccination and postinfection.